Sammy, the Seal - Hoff, Syd, 1912- (New York, Harper, 1959)
Upon discovering what it is like outside the zoo, Sammy decides there is no place like home.
"Reinforced library edition."--Dust jacket.
Booklist
School Library Journal
Horn Book Magazine
2.1
K-3
Keywords: Seals (Animals) -- Fiction; Seals (Animals) -- Fiction